Penerapan Model Pembelajaran SAVI Terhadap Kemampuan Membaca Puisi pada Siswa Kelas IV SD Negeri 61 Lubuklinggau - Mukti, Damacus Krisna; Yohana Satinem; Citra Raflesia (LITERATUR: Jurnal Bahasa, Sastra dan Pengajaran, 2025)
This study aims to determine the application of the SAVI (Somatic, Auditory, Visual, and Intellectual) learning model in completing the ability to read poetry in fourth grade students of SD Negeri 61 Lubuklinggau. This study used a pseudo-experimental method. The population in this study were fourth grade students of SD Negeri 61 Lubuklinggau, totaling 53 students. The sample selected in this study was class IV.A which amounted to 28 students. The data collection techniques in this study were observation, interviews, documentation and tests. The test in question is a poetry reading test with pre-test and post-test assessment stages. The data analysis technique used in this study is to determine the average value of standard deviation, data normality test and t test (hypothesis). The results of this study indicate that the ability to read poetry of fourth grade students of SD Negeri 61 Lubuklinggau after the application of the SAVI learning model (Somatic, Auditory, Visual, and Intellectual) is significantly completed. This is indicated by the average value of students, in the pre-test of 43,43% and in the post-test increased by 72,57% and evidenced by the results of the t-test obtained tcount of 3,337, then the tcount value is compared with the ttable value with dk = 28 - 1 = 27 at the 5% confidence level is 2,052. So the value of tcount ≥ ttable 3,337 ≥ 2,052, meaning Ha is accepted and Ho is rejected. Thus, it can be concluded that the SAVI (Somatic, Auditory, Visual, and Intellectually) learning model can be used as an alternative learning model.   Keywords: SAVI Learning Model, Reading Ability Poetry